Responses of yeasts to hypo-osmotic stress - Kayingo, Gerald (University of the Free State, 2001)
This study examined the responses of yeasts to hypo-osmotic stress with special emphasis to osmolyte export and facilitating proteins. All yeast strains studied (Z rouxii, P. sorbitophila, S. cerevisiae and S. pombe) rapidly release their intracellular osmolytes upon a decrease in external osmolarity (osmotic downshoek or hypo-osmotic shock). Osmolyte release is very rapid, specific and is not affected at reduced temperatures neither inhibited by the channel blocker gadolinium or the protonophore CCCP. The export process is well controlled and the amount of osmolyte released is proportional to the shock intensity. Osmolyte release occurs with minimal cell lysis and thus the survival as well as the subsequent growth of yeast cells is largely unaffected after hypo-osmotic shock. The patterns and export kinetics suggested the involvement of channel proteins similar to that of Fps1p previously reported in S. cerevisiae. However, search for FPS1 homologues from other yeasts using PCR and DNA probes resulted in weak hybridization signals suggesting that the putative glycerol channel encoding genes might have low sequence similarity to FPSl. It appears that although the mechanism of osmolyte release is conserved among yeasts, the proteins involved in this release might be divergent. This finding was in contrast to the general view that most of the genes involved in glycerol metabolism and stress responses such as GPDl (NAD+-dependent glycerol-3- phosphate dehydrogenase), DAKl (dihydroxyacetone kinase) and HOGl (MAP kinase of the HOG pathway) are well conserved in all yeasts. Isolation and cloning of the corresponding genees) involved in osmolyte export will shed more light on the molecular nature and physiological roles of these exporters. In yeast, osmolyte transport across the cell membrane occurs via active transport, mediated by channel proteins and by passive diffusion. The extent to which osmolytes permeates the cell membrane may then be influenced by the membrane lipid composition. In this study, the role of ergosterol (the most abundant sterol in yeast membranes) in osmolyte release and survival of yeast cells during hypo-osmotic stress was investigated. Cells lacking a glycerol facilitator (the fps1∆ strain) grow very poorly upon an osmotic downs hock, but apparently survived the shock better and recovered more rapidly if ergosterol was supplied. Furthermore, the rate and amount of glycerol release was markedly enhanced in the fps1∆ mutant when exogenous ergosterol was supplied. The erg-l disruption mutant which is unable to synthesise ergosterol, survived and recovered from the osmotic shock more successfully at the higher ergosterol concentration. Although the mechanism by which ergosterol improves glycerol release and survival of yeast cells is not well understood, it could presumably be related to the membrane stabilizing effects of ergosterol and the associated improvements in membrane fluidity. The polyene antibiotic nystatin, which affects membrane permeability in an ergosterol dependent way, caused S. cerevisiae cells to release a large amount of glycerol and equally inhibited the growth of wild-type and fsp1 deletion strains in medium containing 5% (w/v) Nael. This study demonstrated the role of ergosterol in glycerol efflux and survival in S. cerevisiae after an osmotic downshock and provided additional evidence for the significance of membrane permeability and glycerol con servation in yeast osmoregulation. The ability to regulate water and solute flux across cell membranes is critical in ensuring a constant turgor pressure as well as the proper functioning of biochemical processes. In most organisms, this process appears to be mediated by the MIP family transmembrane channel proteins, most of which have been characterized in higher animals. An in silicio phylogenetic analysis of microbial MIP channels revealed two major groups, the glycerol facilitators and the water channels (aquaporins), but further divided the glycerol facilitators into two subfamilies. Water channels seem to be important for growth after drastic changes in medium osmolarity, especially to lower osmolarity. Glycerol facilitators appear to exist in all microbial groups where they function in the uptake of glycerol and related compounds for their catabolism. The S. cerevisiae glycerol facilitator has been shown to be involved in osmoregulation by controlling the accumulation and release of glycerol. The occurrence of glycerol facilitators in other yeasts and their role in osmoregulation were investigated in this study. Blast searches in the S. pombe data bases revealed three putative glycerol transport proteins one of which shows considerably structural similarities to known MIP family glycerol facilitators. However, heterologous expression and subsequent functional analysis of this S. pombe mip l did not indicate its involvement in glycerol transport across the plasma membrane. It is still unknown whether the protein is involved in glycerol transport across other organelle membranes or whether it is involved in transport of a yet unidentified solute. The expression of S. pombe mip l is induced by osmotic stress suggesting a role in osmoregulation. However, deletion of S. pombe mip I does not cause any observable effects on growth of S. pombe cells during osmotic stress. Therefore, the physiological role of the S. pombe mipl as well as the actual transporter(s) controlling glycerol flux in S. pombe remains to be elucidated.

Hierdie studie het die respons van giste op hipo-osmotiese spanning ondersoek, veral osmoliet transport en die fasiliterende proteïene. Die studie het getoon dat al die giste- bestudeer (Z.rouxii, P. sorbitophila, S. cerevisiae and S. pombe) intrasellulêre osmoliete vinnig vrystel na dat die eksterne osmolariteit verlaagis (afwaardse osmotiese skok of hipo-osmotiese skok). Die vrystelling van osmoliete vind vinnig en spesifiek plaas en word nie deur verlaagde temperatuur beinvloed. Verder word die proses nie deur die kanaalblokkeerder ganadolium of die protonofoor CCCP geinhibeer nie. Die vrystelling van osmoliete word gereguleer sodat die hoeveelheid osmoliet wat vrygestel word korreleer met die verandering in eksterne osmolariteit. Omdat osmoliet vrysteling met minimale lise van selle plaasvind, word die oorlewing en groei van selle nie deur hipo-osmotiese skok geafekteer nie. Die kinetiese parameters van osmoliet vrystelling was soortgelyk aan die van die FPSl proteien van S. cerevisiae. Hibridisasie eksperimente (PCR en DNA peilers) het egter getoon dat daar 'n laë ooreenkoms tussen DNS volgordes van FPS1 homoloë en 'n moontlike gliserol-kanaal-geen was. Dit blyk dus dat alhoewel die metodes om osmoliete vry te stel in giste gekonserveerd is dat die proteiene betrokke by die vrystelling verskil. Hierdie bevinding verskil van die algemeen aanvaarde opvatting dat die gene, betrokke by gliserol metabolisme en skok respons (bv. GPDl; NAD+-dependent glycerol-3-phosphate dehydrogenase, DAKl; dihydroxyacetone kinase and HOGl; MAP kinase of the HOG pathway), gekonserveerd is in giste. Isolasie en klonering van die geen wat wel betrokke by vrystelling van osmoliete is, sal meer lig werp op die molekulêre aard en fisiologiese rol van transport-proteiene. In giste word osmoliete opgeneem deur aktiewe transport deaur kanaal proteiene, asook passiewe diffusie oor die selmembraan. Die mate waar toe die selmembraan deurlaatbaar is, vir osmoliete, mag bepaal word deur die lipied samestelling van die selmembraan. In hierdie studie is die moontlike rol van ergosterol (die mees algemene lipied in gis selmembrane) in die vrysteling van osmoliete tydens hipo-osmotiese spanning ondersoek. Selle sonder 'n gliserol fasiliteerder (fps1∆ stain) het swak gegroei na 'n afwaardse osmotiese skok, maar indien ergosterol in die medium ingesluit is het sulke selle beter oorleef en vinniger herstel. Verder het die tempo waarteen gliserol deur die fps1∆ stain vrygestel is merkbaar verhoog in die teenwoordigheid van eksterne ergosterol. Die erg-1 disrupsie mutant, wat nie ergosterol kan sintetiseer nie, het ook beter oorleef en herstel in die teen woordigheid van eksterne ergosterol. Alhoewel die meganisme van bogenoemde effek van ergosterol op gliserol vrystelling onbekend is. is dit waarskynlik a.g.v. die stabiliseering en verbetering is selmembraan vloeibaarheid. Die antibiotikum nystatin, wat membraan deurlaatbaarheid op 'n ergosterol afhanklike wyse beinvloed, het veroorsaak dat S.cerevisiae selle groot hoeveelhede giserol vrystel en het dus die groei van wilde tipe ea fps1 ∆ delesie mutante in 5% (w/v) Nael geinhibeer. Hierdie studie het getoon dat ergosterol 'n rol speel in die vrylating van gliserol uit selle asook in die oorlewing van S. cerevisiae na osmotiese skok. Dit verskaf ook verdere bewys vir die belangrikheid van membraam deurlaatbaarheid en gliserol bewaring in osmoregulering van giste. Dit was duidelik dat die vermoë van selle om die beweging van water en ander oplosmiddels oor selmembrane te beheer belangrik is in die handhawing van korrekte turgordruk en biochemiese funksionaliteit. In meeste organismes blyk dit dat die proses deur transmembraanproteiene van die MIP familie beheer word. 'n "in silico" filogenetiese analise van mikrobiese kanaalproteiene het getoon dat daar twee hoofgroepe IS nl. gliserolfasiliteerders en waterkanale (aquaporins). Die gliserol fasiliteerders was onderverdeel in twee groepe. Die waterkanale blyk belangrik te wees vir groei na verandering in medium osmolaritiet, veral verandering na laë osmolariteit. Gliserol fasiliteerdes kom waarskynlik in alle mikrobe organismes voor en speel 'n rol in die opname van gliserol en verbindings betrokke by gliserol katabolisme. Die gliserol fasiliteerder van S. cerevisiae beheer osmoregulering deurdat dit die opname of vrystel van gliserol kontroleer. Die voorkoms van gliserolfasiliteerders in ander giste en hulle rol in osmoregulering is in hierdie studie ondersoek. "BLAST" ondesoeke van DNS data van S. pombe het drie moontlike gliserol fasiliteerders van die MIP familie getoon. Heteroloë uitdruking en funksionele analises van S. pombe mip1 kon egter geen bewys lewer dat dit betrokke is in gliserol transport oor die plasma membraan. Dus is dit nog onbekend of die proteïen betrokke is by gliserol transport oor ander organel membrane en of dit betrokke is by die transport van ander oplosmiddels. Uitdruking van S. pombe mipI word deur osmotiese spanning geinduseer, wat 'n rol daaarvoor tydens osmoregulering aandui. Delesie van S. pombe mip l het egter nie die groei van S. pombe tydens osmotiese spanning geaffekteer nie. Die fisiologiese rol van S. pombe mipl en die werklike transporter(s) wat gliserol opname/vrystelling beheer in S. pombe moet dus nog ontrafel word.
Thesis (Ph.D. (Microbiology and Biochemistry))--University of the Free State, 2001
Keywords: Osmoregulation; Yeast -- Fungi -- Effect of stress on; Yeast -- Physiology